“My One Story is Hunger”: il languore metafisico delle protagoniste di Anzia Yezierska (Altre Modernità, 2015)
This essay focuses on “hunger”, the Leitmotif of Anzia Yezierska's literary production, a powerful mixture of feelings experienced by her protagonists, Jewish women born and raised in the poverty and oppression of the shtetlach under the Czarist domination, who fled to America in the 1880s to look for opportunities of freedom, spiritual development and personal growth that they believed they could find only in the New World. Sadly, their longing turns out to be a metaphysical one that can never be satisfied, which consigns them to a destiny of messianic wait and unfulfilled desire where hunger remains the only possible existential dimension, i.e. their one story.